Case Report: Fatal presumptive idiosyncratic hepatic necrosis secondary to standard-dose leflunomide administration in a dog - Aponte-Colon, Cristina; Cochran, Lauren A.; Harris, Lauren; Mears, Erick A.; Frederick, Steven W. (Frontiers in Veterinary Science, 2025)
An 8-year-old neutered male Greyhound was presented with intermittent lameness and joint pain, leading to a diagnosis of idiopathic immune-mediated polyarthritis. The initial treatment regimen involved prednisone and minocycline. Leflunomide (3 mg/kg PO q24h) was prescribed later for secondary immune modulation. Five weeks later, the dog exhibited signs of acute lethargy, weakness, and increased liver enzyme activities (alanine aminotransferase [ALT] 6,613 U/L and aspartate aminotransferase [AST] 3,718 U/L). Despitereceiving supportive care, the dog died. Necropsy revealed massive hepatic necrosis with effaced hepatic architecture and centrilobular pools of free blood, similar to findings noted in people with leflunomide-induced hepatic injury. This case highlights a previously unreported severe, idiosyncratic hepatotoxicity associated with standard doses of leflunomide in dogs, illustrating the need for vigilant monitoring and increased awareness of the potential need for dose adjustment if liver enzyme elevations occur.